New Ecological Paradigm: Testing the Environmental Concern Among Urban Middle Income Cebu City Household Heads - Chaves, Mary Gretchen F. (JPAIR Multidisciplinary Research, 2012)
This study evaluates the level of environment concern among middle income Cebu City household heads using the 15-item New Ecological Paradigm (NEP) scale developed by Dunlap et al (2000). Environment concern as a pro-environmental attitudinal construct reflects a person’s eco-centric orientation. The NEP scale is a globally accepted methodological assessment for pro-ecological worldview wherein the more an individual agrees with the NEP items, the more concerned (s)he is about the environment. Also investigated in the study are the underlying dimensions (subscales) of the NEP scores. The results of the study show the respondents’ NEP scale items’ average score as "unsure" indicating neither strong or weak environment concern. Using principal components analysis, three subscales were generated, explaining 77% of the variance, and are interpreted in this study as "disastrous consequence of ecological abuse", "delicate balance of nature," and "humans subject to law of nature". The study concludes that while respondents agree with the disastrous consequences att ributed to ecological abuse, the NEP scores indicate low level of environment concern. The results of this study serve as reference to the recommendations raised intended to improve the ecological worldview among the respondents to favor the environment, particularly on education and information campaigns.